Mindfulness Intervention Reduces Care Burden Status of Family Caregivers for the Elderly: A Systematic Review - Syahrani Iskandar; Etty Rekawati; Kuntarti Kuntarti (GLOBAL HEALTH SCIENCE GROUP, 2025)
ABSTRACT The increasing elderly population in Indonesia poses significant challenges for families acting as caregivers responsible for providing optimal care. Caregivers often experience physical, mental, and emotional stress, commonly referred to as caregiver burden. Mindfulness therapy has emerged as an effective approach to reducing stress by transforming negative thought patterns. Objective: This study aims to evaluate the effectiveness of mindfulness interventions in reducing caregiver burden and enhancing the health and well-being of caregivers for elderly family members through a systematic review. Method: A systematic review was conducted using the PRISMA approach. Data were collected from three databases: PubMed, EBSCOHost, and Scopus, with inclusion criteria focusing on research articles evaluating the effectiveness of mindfulness for caregivers of the elderly, published between 2019–2024. Five studies with a Randomized Controlled Trial (RCT) design were thoroughly analyzed using the Critical Appraisal Skills Programme (CASP). Results: The findings revealed that mindfulness interventions significantly reduced stress levels, depressive symptoms, and anxiety among caregivers. Additionally, improvements in sleep quality and emotional well-being were noted in some studies. While the effect on reducing caregiver burden was inconsistent, most studies demonstrated significant enhancements in mental health and overall well-being. Conclusion: Mindfulness-based interventions have proven effective in supporting the physical and mental health of caregivers for the elderly.